Dimension Estimate for the Global Attractor of an Evolution Equation - Renato Colucci (Abstract and Applied Analysis, 2012)
We estimate the dimension of the global attractor of an evolution equation by the study of the evolution of the n-dimensional volumes under the flow. We compare these results with the estimate of the dimension of the inertial manifold.